2006
DOI: 10.3892/ijo.29.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lung cancer with siRNA targeting PTTG

Abstract: Abstract. Pituitary transforming gene (PTTG) is frequently expressed at high levels in malignant tumors. We report high levels of expression of PTTG in various lung tumors and tumor-derived cell lines. For a better understanding of its role in maintaining the cancer phenotype, we used RNA interference (RNAi) directed against PTTG. Transfection of H1299 cells with PTTG siRNA duplex (5'-UGG GAG AUC UCA AGU UUC A-3') to a final concentration of 100 nmol/l resulted in almost complete depletion of PTTG mRNA within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…Based on these results, we hypothesized that a correlation exists between the level of expression of PTTG and tumorigenesis, and that down-regulation of PTTG expression in tumors will lead to suppression of tumor growth and development. In our recent studies, we showed that down-regulation of PTTG in lung tumor cells (H1299) by PTTG siRNA resulted in the inhibition of colony formation in vitro and tumor development and growth in nude mice (6). Consistent with our results, Cho-Rok et al (24), using an adenovirus system expressing PTTG siRNA to downregulate PTTG expression, recently showed a significant reduction in tumor growth in vitro and in vivo for hepatoma cells.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Based on these results, we hypothesized that a correlation exists between the level of expression of PTTG and tumorigenesis, and that down-regulation of PTTG expression in tumors will lead to suppression of tumor growth and development. In our recent studies, we showed that down-regulation of PTTG in lung tumor cells (H1299) by PTTG siRNA resulted in the inhibition of colony formation in vitro and tumor development and growth in nude mice (6). Consistent with our results, Cho-Rok et al (24), using an adenovirus system expressing PTTG siRNA to downregulate PTTG expression, recently showed a significant reduction in tumor growth in vitro and in vivo for hepatoma cells.…”
Section: Resultssupporting
confidence: 77%
“…To assess in vivo activity of PTTG silencing, A2780 cells transfected with control plasmid, control siRNA, or PTTG siRNA were trypsinized, washed twice with PBS, and resuspended in RPMI media without serum and antibiotic. Cells (2x10 6 /site) were injected subcutaneously into both flanks of 4 to 6-week-old nu/nu mice (NCI). Five mice were used in each group.…”
Section: Colony Formation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In the lung cancer cell line H1299 [120], a 60% reduction in PTTG protein resulted in null males can be rescued from diabetes development by undergoing surgical gonadectomy followed by estradiol treatment through increased serum adiponectin levels resulting in increased insulin sensitivity [122]. As a follow-up study, the mechanism of reduced pancreatic ~-cells proliferation by PTTG deletion was determined [123].…”
Section: Pttg In Cancermentioning
confidence: 99%
“…Due to the lack of specific ovarian promoter, we selected a strong non-specific CMV promoter, to induce the necessary level of PTTG to achieve this biological function, as the level of PTTG is critical for tumorigenesis [116,120] . However, due to the nature of this promoter, it was necessary to analyze other tissues to determine if tumorigenesis has occurred.…”
Section: Tgpttgp53+mentioning
confidence: 99%